Enriching Soil Organic Carbon for Sustainable Agriculture, Food Security, and Health - Amanullah; Urooj Khan (Pusbindiklatren Bappenas, 2024)
Amidst a growing global population and climate change challenges, this paper examines the vital role of soil organic carbon (SOC) in sustainable agriculture. Enriching SOC enhances soil fertility, crop productivity, and carbon sequestration, mitigating climate impacts. Prioritizing SOC improves soil structure, water retention, and nutrient availability, raising crop quality. Methodologically, the study combines normative juridical analysis with a qualitative literature review. Results highlight SOC's importance in fostering resilient agriculture and food security despite coordination challenges in policy formulation. Recommendations include incentivizing SOC-enhancing practices, investing in awareness, and fostering multi-stakeholder collaboration. Prioritizing SOC enriches agricultural policies, ensuring sustainable practices, food security, and human well-being, offering a pathway to resilient agriculture and a sustainable future.